Comparison of happiness in students of a public and private university in Peru - Walker Aragon-Cruz; Sonia Laura-Chauca; Percy Gómez-Bailón; José Fuentes-López; Katia Barrientos-Paredes; María Bedoya-Gonzales; Yudi Yucra-Mamani; Claudia Flores-Gutiérrez; Marco Cossio-Bolaños; Rossana Gomez-Campos (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Happiness is a positive component of mental well-being. In young university students, it is linked to ideals in many areas, such as physical health, mental health, harmonious inter-personal relationships, academic performance, and professional success. The aim of the study was to compare the happiness of university students from a state and private university according to professional areas and age range. MATERIALS AND METHODS: A descriptive cross-sectional study with selected 312 university students was conducted. The age range was from 17 to 32 years. The two professional areas surveyed were health sciences and engineering. Happiness was measured using a scale with 11 questions and four dimensions [1: Positive sense of life (three questions), 2: Satisfaction with life (three questions), 3: Personal fulfilment (two questions), and 4: Joy of living (three questions)]. The normality of the data was verified. Differences between sexes, areas, universities and ages were verified by t-test for independent samples. Differences between age ranges were verified by Anova. RESULTS: This study showed that there were no differences in happiness between EU and UP students when compared by gender, professional area, and age ranges. CONCLUSIONS: These results suggest that during the period of university studies, happiness values remain stable in both types of universities.